Analysis of Internet Service Provider Selection Using the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) Methods - Hati, Shinta Wahyu; Rahayu, Yunita (Journal of Applied Business Administration, 2025)
Currently, the need for an internet connection is increasing due to the human need for information and communication that can be obtained through the internet. A decision support system with criteria is needed to solve the challenge of choosing an internet package with many components or criteria that must be evaluated. Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) are two multi-criteria decision support system techniques, but they use different measurement techniques. This research aims to identify the best Internet Service Provider by applying the Simple Additive Weight (SAW) and Analytic Hierarchy Process (AHP) techniques. The objects used in this research are the providers Indihome, Biznet, and Solnet. The weight of each criterion is determined using the AHP technique, and the best suppliers are ranked using the SAW approach. The sampling technique used in this research was Purposive Sampling. In this study, the ranking results of 100 respondents showed that the ranking for the AHP method was 60% and for the SAW method was 92%. Thus, global calculations using the AHP and SAW methods were obtained for the best alternative ISP, namely Indihome.